Regulatory T Cells in Allergy and Asthma - Martín-Orozco, Elena; Norte-Muñoz, María; Martínez-García, Javier (Frontiers in Pediatrics, 2017)
The immune system’s correct functioning requires a sophisticated balance between responses to continuous microbial challenges and tolerance to harmless antigens, such as self-antigens, food antigens, commensal microbes, allergens, etc. When this equilibrium is altered, it can lead to inflammatory pathologies, tumor growth, autoimmune disorders, and allergy/asthma. The objective of this review is to show the existing data on the importance of regulatory T cells (Tregs) on this balance and to underline how intrauterine and postnatal environmental exposures influence the maturation of the immune system in humans. Genetic and environmental factors during embryo development and/or early life will result in a proper or, conversely, inadequate immune maturation with either beneficial or deleterious effects on health. We have focused herein on Tregs as a reflection of the maturity of the immune system. We explain the types, origins, and the mechanisms of action of these cells, discussing their role in allergy and asthma predisposition. Understanding the importance of Tregs in counteracting dysregulated immunity would provide approaches to diminish asthma and other related diseases in infants.